Meta-analysis of Postoperative Incision Infection Risk Factors in Colorectal Cancer Surgery - Rehman, Waheed Ur; Khan, Zoya Hussain; Ullah, Fayaz; Khan, Muhammad Kaleem; Qader, Rayyan; Bahadur, Saddam; Muhammad, Saqib (Infectious Diseases Journal of Pakistan, 2023)
Background: Colorectal cancer (CRC) is a highly prevalent type of malignancy in the world and surgical resection is considered as the main curative method. However, postoperative surgical site infections (SSIs), particularly incisional SSIs, remain a frequent complication, affecting 5–20% of patients and leading to prolonged hospitalisation, increased healthcare costs, and poorer oncological outcomes. This meta-analysis aimed to identify and quantify patient- and surgery-related risk factors for incisional SSIs following colorectal cancer surgery, in alignment with the PICO framework. Material and Methods: PubMed, Embase, Web of science and Cochrane library were systematically searched until 2023 to find the studies published between 2000 and 2023. Eligible studies included adult CRC patients undergoing open or laparoscopic resection reporting risk factors for incisional SSIs. The items used to assess the risk of bias were the Newcastle-Ottawa Scale (NOS) instrument of observational studies and the Cochrane Risk of Bias tool of trials. Random-effects model estimates were used to calculate pooled odds ratios (ORs) with 95% confidence intervals (CI) and heterogeneity was quantified using I² statistic. Results: Ten eligible studies encompassing 286,690 patients were included. Significant modifiable risk factors included BMI ≥30 kg/m² (OR = 1.89, 95% CI: 1.55–2.29), diabetes mellitus (OR = 1.72, 95% CI: 1.43–2.06), operative time >3 hours (OR = 1.58, 95% CI: 1.34–1.87), high blood loss (OR = 1.66, 95% CI: 1.31–2.11), and open surgery (OR = 2.13, 95% CI: 1.78–2.54). Non-modifiable factors included male sex and higher ASA scores. Conclusion: Obesity, diabetes, prolonged surgery, and open approach are major modifiable risk factors for incisional SSIs after CRC surgery. Targeted perioperative optimization can reduce infection risk and improve outcomes. Keywords: Colorectal cancer, Surgical site infection, Incision infection, Risk factors, Postoperative complications, Meta-analysis